How attitudes may affect the success of inclusion - Luebke, Kristene (My University, 1998)
This analysis explores the current literature about the inclusion of students with disabilities in regular physical education. With increasing numbers of students with disabilities being educated in the mainstream, it is crucia1 that educators understand the concept of inclusion and what it takes for inclusion to succeed. Physical educators need to be aware of the existence of negative attitudes toward inclusion and the impact they have on successful integration. Although the components of inclusion are clearly documented, the method in which the model is incorporated varies widely from classroom to classroom. Agreement exists that there is a spectrum of placement options available for the child with disabilities and the vehicle for providing service is es unique as the child. Inclusion has many benefits, but in order to be successful, there are some key components that must exist in order to decrease resistance and increase the acceptance of students with disabilities in the regular physical education environment. Collaboration, communication, and cooperation are crucial among all school staff members working with children with disabilities. Without these components, frustration may occur which can lead to negative attitudes. The experience the teacher has working with students with disabilities is linked to the success of inclusion. Universities and school districts need to address the training received by educators. Teachers should be better prepared to deal with a variety of disability types. Additional training, coursework, and in-service offerings are suggestions to improve the educator's experience in working with students with disabilities. The need to improve the attitude of the educator appears to be tho starting point to the success or failure of inclusion. More research is needed into the formation of attitudes and how to go about changing attitudes.
Keywords: Physical education teachers - Attitudes; Inclusive education; Physical education for children with disabilities